1962
DOI: 10.1113/jphysiol.1962.sp006830
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation volume as a stimulus to spontaneous ventilation after prolonged artificial ventilation

Abstract: The observations reported in this paper are intended to determine whether the ventilation volume imposed during artificial ventilation has an effect on subsequent spontaneous ventilation. It reports investigations on paretic patients in which the tidal volume imposed during artificial ventilation was varied, but the end-tidal PCO2 and the ventilatory frequency were kept constant. A variable volume of external dead space was introduced during artificial ventilation. Periods of spontaneous ventilation were subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
3

Year Published

1962
1962
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 10 publications
0
14
3
Order By: Relevance
“…As the level of pCO2 rises during the experiment, so a ventilatory response occurs and the ventilation increases during the rebreathing periods. It has been shown that hyperventilation may cause the central respiratory mechanisms to habituate to a new level of ventilation even when the pCO2 is prevented from falling [Smith et al, 1961]. In our experiments, a short period of severe isocapnic hyperventilation did not displace the breath holding-CO2 response curve, which suggests that the pattern of breathing has little effect on a subsequent breath hold.…”
Section: Discussioncontrasting
confidence: 40%
“…As the level of pCO2 rises during the experiment, so a ventilatory response occurs and the ventilation increases during the rebreathing periods. It has been shown that hyperventilation may cause the central respiratory mechanisms to habituate to a new level of ventilation even when the pCO2 is prevented from falling [Smith et al, 1961]. In our experiments, a short period of severe isocapnic hyperventilation did not displace the breath holding-CO2 response curve, which suggests that the pattern of breathing has little effect on a subsequent breath hold.…”
Section: Discussioncontrasting
confidence: 40%
“…Smith et al (181,182) found that in partially paralyzed individuals, altered ventilation or ventilatory pattern imposed by a respirator tended to perpetuate itself when the respirator was discontinued. This was demonstrable when the PCO, was kept constant by varying the dead space of the respiratory support circuit, but the greatest persistence of ventilation occurred when hypocapnia was allowed to develop.…”
Section: Role Of Hypocapniu and Hyperventilationmentioning
confidence: 99%
“…1, 2). This is due to the part played by ventilation volume in spontaneous ventilation in these circumstances (Smith et al 1962); the presence of the horizontal portion of the curve does not alter the position of the steep part. The change in V/pCO2 curves which occurs within a few hours may take the form of either a lateral shift or a change in slope.…”
Section: Discussionmentioning
confidence: 94%
“…which is less than the upper-airway dead space eliminated by the tracheotomy. Details of the artificial ventilation and of the methods of C02 AFTER ARTIFICIAL VENTILATION 33 measuring ventilation volume (V) and end-tidal pCO2 during artificial and spontaneous ventilation have already been described (Smith, Spalding & Watson, 1962). All gas volumes are expressed at ambient temperature and pressure, and saturated with water vapour.…”
Section: Methodsmentioning
confidence: 99%